2017
DOI: 10.1002/adfm.201604635
|View full text |Cite
|
Sign up to set email alerts
|

Strong Facet Effects on Interfacial Charge Transfer Revealed through the Examination of Photocatalytic Activities of Various Cu2O–ZnO Heterostructures

Abstract: Confirming the photocatalytic inactivity of Cu2O nanocubes through the formation of Au‐decorated–Cu2O heterostructures, spiky ZnO nanostructures are grown on Cu2O cubes, octahedra, and rhombic dodecahedra to demonstrate that charge transfer across semiconductor heterojunctions is also strongly facet dependent. Unintended CuO formation in the growth of ZnO on perfect Cu2O cubes makes them slightly active toward methyl orange photodegradation. Under optimal ZnO growth conditions without CuO presence, Cu2O cubes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 121 publications
(83 citation statements)
references
References 36 publications
(46 reference statements)
3
80
0
Order By: Relevance
“…Theo bserved large facet-dependent photocatalytic properties of polyhedral Cu 2 O, TiO 2 ,a nd other semiconductors can be similarly explained, as the efficiency of photoexcited charge migration to external surfaces or heterojunctions strongly depends on the contacting faces. [7][8][9][10][11][12][13] Furthermore,this thin layer with dissimilar band structures for different surface planes also gives rise to the observed facet-dependent optical absorption and emission properties in semiconductor nanocrystals and quantum nanostructures that has been recognized recently. [13][14][15][16][17][18] Since facet effects are observable in many semiconductor materials,i ti s highly interesting to examine possible existence of facetdependent electrical properties of silicon.…”
mentioning
confidence: 89%
“…Theo bserved large facet-dependent photocatalytic properties of polyhedral Cu 2 O, TiO 2 ,a nd other semiconductors can be similarly explained, as the efficiency of photoexcited charge migration to external surfaces or heterojunctions strongly depends on the contacting faces. [7][8][9][10][11][12][13] Furthermore,this thin layer with dissimilar band structures for different surface planes also gives rise to the observed facet-dependent optical absorption and emission properties in semiconductor nanocrystals and quantum nanostructures that has been recognized recently. [13][14][15][16][17][18] Since facet effects are observable in many semiconductor materials,i ti s highly interesting to examine possible existence of facetdependent electrical properties of silicon.…”
mentioning
confidence: 89%
“…In another work, it was revealed that photoactive Cu 2 O octahedras became inactive after the deposition of ZnO. [156] The result was explained by unfavorable band alignment at the interface between ZnO (101) and Cu 2 O (111).…”
Section: Mismatch Between Light Absorbers and Guest Materialsmentioning
confidence: 99%
“…This model is also very useful to explain widely observed facet-dependent photocatalytic properties of many semiconductor materials and heterostructures, in which photocatalytic activities can vary from highly active to completely suppressed depending on the exposed or contacting facets as seen in Cu 2 Oc rystals and Cu 2 O-ZnOh eterostructures. [9][10][11][12][13][14][15] As the ultrathin layer has dissimilar band structures for different crystal faces it meanst hat light of somewhat differentw avelengths is absorbed by particles of variouss hapes, accounting for the observedf acet-dependent opticalp roperties of Cu 2 Oa nd other semiconductor crystals. [7,11,[16][17][18] To verify that the facet-dependent electrical-conductivity phenomenon is broadly observable in semiconductors, electrical-conductivity measurementsh ave been made on four different faces of Si wafers, which revealed that the (111)a nd (112) surfaces are highly conductive.…”
Section: Introductionmentioning
confidence: 99%